'Sustainable Mining'? Corporate Social Responsibility, Migration and Livelihood Choices in Zambia. Issue 11 (1st November 2016) - Gilberthorpe, Emma; Agol, Dorice; Gegg, Thomas
Abstract: Whilst corporate social responsibility is now part and parcel of many multinational mining operations, and a 'sustainable mining' narrative a fundamental part of their public persona, companies still struggle to provide secure, long-term livelihoods for either locals or the swathe of migrants mining attracts. Minimal opportunities in the formal sector leave migrants in particular engaging in informal and illegal activities that offer poor livelihood security. In this paper we examine these activities in northern Zambia's emerald mines to highlight some of the issues and barriers to sustainable development that exist across mining zones. We conclude that livelihood choices are not augmented by a so-called 'sustainable mining' approach that fails to engage all sectors of the population. We show the numerous challenges faced by migrants in this part of Zambia to accentuate the factors that need to be addressed before favourable environments for fostering sustainable mining might be achieved.